Spectral CT imaging as a new quantitative tool? Assessment of perfusion defects of pulmonary parenchyma in patients with lung cancer - Sun, Ying-Shi; Zhang, Xiao-Yan; Cui, Yong; Tang, Lei; Li, Xiao-Ting; Chen, Ying; Zhang, Xiao-Peng (Chinese Journal of Cancer Research; Vol 25, No 6 (December 26, 2013): Chinese Journal of Cancer Research, 2013)
Objective: This study investigated the capability of dual-energy spectral computed tomography (CT) to quantitatively evaluate lung perfusion defects that are induced by central lung cancer. Methods: Thirty-two patients with central lung cancer underwent CT angiography using spectral imaging. A univariate general linear model was conducted to analyze the variance of iodine concentration/CT value with three factors of lung fields. A paired t-test was used to compare iodine concentrations and CT values between the distal end of lung cancer and the corresponding area in the contralateral normal lung. Results: Iodine concentrations increased progressively in the far, intermediate and near ground sides in the normal lung fields at 0.60±0.28, 0.93±0.27 and 1.25±0.38 mg/mL, respectively (P